Evaluation of The Occurrence Of Sharp Instrument Accidents in a Clinical Dentistry School - Vanessa Pereira Gonçalves de Souza; Valéria Cristine Engrácio Borges; Orlando Francisco Barbosa Nascimento; Jéssica Thayse Virginio Alcântara Duca; Denise Rodrigues Cavalcanti Veras; Olívia Maria Guimarães Marroquim; Aurea Valéria de Melo Franco (Associação Brasileira de Odontologia, 2018)
Objective: to evaluate the occurrence of occupational accidents with undergraduate dentistry students from the 5th to 10th period of Centro Universitário Cesmac. Material and Methods: analysis of the notification forms of accidents with exposure to blood or other biological materials, between the years of 2011 to 2016, available on the Biosafety Committee of Centro Universitário Cesmac. Results: we observed that the highest number of accidents occurred in 2014 and that the most common instruments were the needle of the carpule syringe, followed by the periodontal curette. Most accidents occurred during the moment of care. Conclusion: the students were submitted to the experience of accidents with potential of biological contamination because of sharp instruments. Strengthening prophylactic measures is needed to reduce such circumstances that are detrimental to the health of those involved in the patient and student relationship.